Survey of diseases caused by Fusarium spp. on palm trees in the Canary Islands - Hernández-Hernández, Julio; Espino, Ana; Rodríguez-Rodríguez, Juan; Pérez-Sierra, Ana; León, Maela; Abad-Campos, Paloma; Armengol, Josep (Phytopathologia Mediterranea, 2010)
Between 2006 and 2007, palm trees growing in both gardens and public parks and natural palm groves in the Canary Islands (Spain), and showing symptoms of wilt and dieback, were surveyed. Isolates were recovered from affected tissues of the crowns, leaves and vascular fragments on potato dextrose agar (PDA). After incubation, the Fusarium spp. colonies recovered were single-spored. They were transferred to PDA and Spezieller Nahrstoffarmer Agar (SNA) for morphological identification. Identification of Fusarium oxysporum f. sp. Canariensis was confirmed by PCR with the specific primers HK66 and HK67, which amplified a fragment of 567 bp. Fusarium wilt caused by F. oxysporum f. sp. canariensis was found on 54 Phoenix canariensis trees growing on four islands: Gran Canaria, Fuerteventura, La Palma and Tenerife. F. proliferatum occurred on fifteen palms (10 P. canariensis, 1 P. dactylifera, 3 Roystonea regia and 1 Veitchia joannis) located in Gran Canaria, Fuerteventura and Tenerife. Both these Fusarium species were found only in diseased palms from gardens and public parks, but not in natural palm groves. The results show that Fusarium wilt of P. canariensis is common in the Canary Islands and for the first time report F. proliferatum affecting different palm species in those islands.